HARVESTING PEACE: CHRISTIAN-MUSLIM RELATIONSHIP IN BARANGAY KAKAI RENABOR, THE PHILIPPINES - Akhmad Siddiq (Jurnal Kajian Wilayah, 2015)
Barangay Kakai Renabor is a small district in Lanao Del Norte, Philippine. It is renowned as the area of conflict.Christians and Muslims used to fought one another, and living in emotional tension that guided them to commitvarious violences. Disharmonious relationship was exist because every group insists to live exclusively in Barangay,and striving to eliminate the existence of others. There were only two choices: Christians without Muslims or Muslims without Christians. So did their previous story. Recently, they live conjointly harmoniously. They work cooperatively both in planting and harvesting. Indeed, they do it in one similar terrain. Christians and Muslims bury their bad memories and wounds. They live side by side with the spirit of mutual respect and mutual understanding inthe Barangay community. This paper aims to discuss the conflict transformational process which has accomplished in order to reconcile Christians and Muslims, how they overcomed tensions, and what they required to develop a better future. In doing so, this paper will describe how they solved the conflict, what sort of tools they used, and what the expected-future they need.Keywords: Christians-Muslims relationship, violence, peace, and conflict transformation.